Development of a patient-robot interface for a long-term interaction in cardiac rehabilitation at fundación cardioinfantil - instituto de cardiología (2020)
According to the World Health Organization, Cardiovascular diseases (CVDs) are the first cause of death worldwide. An estimated 17.9 million people die each year because of CVDs. In order to treat the consequences and improve the quality of life of the patients affected by these diseases, Cardiac Rehabilitation (CR) is developed. CR is a strategy that consists commonly in different phases with an established number of sessions (e.g., 20-36 sessions). CR is based mainly on exercise procedures and educational approaches. The main goals of CR are to achieve a full patient recovery, in terms of reach optimal physical, mental and social status, and modify the coronary risk factor to reduce subsequent mortality due to cardiovascular illnesses. However, there is evidence that adherence to the CR programs is very low, less than 50% of patients assist actively in the rehabilitation. This limitation can cause major public health issues and negative effects on the patients’ health. In this context, different applications can be used to motivate the patients and enhance the engagement to the rehabilitation. This master thesis presents the evaluation and integration of a patient-robot interface for CR in two studies. The first study (Study I) assess the effects of a socially assistive robot in a control vs a robot without personalized behavior scenario, through qualitative and quantitative parameters. The second study ( Study II) presents the integration of a multi-modal open set identification system and the evaluation of this strategy within a memory scenario. A total of 36 patients were evaluated in this master thesis (15 for the control and robot scenario; and 6 for the memory robot scenario). These patients perform on average 36 sessions of phase II of the CR program. Overall, the results regarding the physiological parameters do not show differences between groups due to the variability of the data and its high dependence on external factors. In contrast, qualitative results show that the patients recommend the use of the robot in CR and they feel more secure thanks to the on-line monitoring. However, clinicians and patients suggest improving the social behaviors of the robot. Thus, in Study II a memory module was implemented. In this case, the outcomes show that the patients perceive the social presence of the robot as they elucidate positive and negative attitudes towards the robot role. Concluding, this master thesis presents the results of the patient robot interface in a long-term/ real-world scenario, demonstrating that SAR holds the promising potential to be a feasible approach that enhances CR programs, increase the adherence to these programs and help to improve the quality of life of cardiac patients.